2020
DOI: 10.1002/marc.202000294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chain‐End Chemistries on the Efficiency of Coupling Antibodies to Polymers Using Unnatural Amino Acids

Abstract: Novel conjugates that incorporate strategies for increasing the therapeutic payload, such as targeted polymeric delivery vehicles, have great potential in overcoming limitations of conventional antibody therapies that often exhibit immunogenicity and limited drug loading. Click chemistry has significantly expanded the toolbox of effective strategies for developing hybrid polymer‐biomolecule conjugates, however, effective systems require orthogonality between the polymer and biomolecule chemistries to achieve e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The disappearance of the SDS-PAGE band for Tf-OMSEA and the appearance of long tailing bands toward the high-molecular-weight region also verified the successful synthesis of the Tf-polymer conjugates (Figure d). This observed streaking effect for protein–polymer conjugates is a well-known phenomenon in PAGE and is attributed to molar mass dispersity, shape of the materials, and the hindrance from the polymeric component when moving through the gel. , …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The disappearance of the SDS-PAGE band for Tf-OMSEA and the appearance of long tailing bands toward the high-molecular-weight region also verified the successful synthesis of the Tf-polymer conjugates (Figure d). This observed streaking effect for protein–polymer conjugates is a well-known phenomenon in PAGE and is attributed to molar mass dispersity, shape of the materials, and the hindrance from the polymeric component when moving through the gel. , …”
Section: Resultsmentioning
confidence: 86%
“…This observed streaking effect for protein−polymer conjugates is a well-known phenomenon in PAGE and is attributed to molar mass dispersity, shape of the materials, and the hindrance from the polymeric component when moving through the gel. 59,60 Following successful synthesis, the Tf-PMSEA and Tf-POEGA conjugates were fluorescently labeled with two fluorophores by reacting the azide-containing monomer in the polymer chain with Cy5 DBCO and Tf protein with Cy7.5 NHS ester to enable the separate visualization of the polymer and protein in subsequent in vivo investigations. A sample of unconjugated Tf was also separately labeled with the Cy7.5 NHS ester as a control for comparison with the Tf-polymer conjugates (Figure 3e).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this recently published study, the nanobody‐conjugated particles showed increased cell association in spheroid models through confocal microscopy [20] . Likewise, ScJ591 has also been expressed with azide functionality and conjugated to a polymer showing high conjugate cell association through flow cytometry [9a] . Interestingly, lower cell associations were observed for 2 K mPEG conjugates compared to all other tested formats (Figure 3A), which is most likely due to partial masking of the protein by linear PEG under the conditions of the experiment.…”
Section: Resultsmentioning
confidence: 88%
“…Hence position 42, a protruding loop structurally far from the CDRs of JVZ007 [15] (a prostate‐specific membrane antigen (PSMA) binding nanobody) was selected as the mutation site for incorporating tetrazine functionality (Figure 1, right). However, it was anticipated that an N‐terminal positioning for ScJ591 (scFv derived from PSMA binding monoclonal antibody J591 [16] ) would not significantly interfere with binding, based on structural analysis and previous work in our labs [9a] . In both cases, the C‐terminal appeared to be a far better positioning for conjugation purposes.…”
Section: Resultsmentioning
confidence: 96%
“…The RJPs described above were modified with a dibenzocyclooctyne (DBCO)‐oligonucleotide (DNA2), and the glass surface was functionalized with the azide group and was conjugated with another DBCO‐oligonucleotide (DNA1). [ 46,51–53 ] As shown in Figure 5c, in the presence of the target DNA, the RJPs were aligned on the surface in the same orientation, resulting in enhanced retroreflective signals compared to the background.…”
Section: Resultsmentioning
confidence: 99%